Mechanical allodynia and enhanced responses to capsaicin are mediated by PI3K in a paclitaxel model of peripheral neuropathy - Adamek, Pavel; Heles, Mario; Palecek, Jiri (Neuropharmacology, 2019)
Paclitaxel chemotherapy treatment often leads to neuropathic pain resistant to available analgesic treatments. Recently spinal Toll-like receptor 4 (TLR4) and the transient receptor potential cation channel subfamily V member 1 (TRPV1) were identified to be involved in the pro-nociceptive effect of paclitaxel. The aim of this study was to investigate the role of phosphatidylinositol 3-kinase (PI3K) and serine/threonine kinases in this process, with the use of their antagonists (wortmannin, LY-294002, and staurosporine). The single paclitaxel administration (8 mg/kg i.p.) in mice induced robust mechanical allodynia measured as a reduced threshold to von Frey filament stimulation and generated reduced tachyphylaxis of capsaicin-evoked responses, recorded as changes in mEPSC frequency in patch-clamp recordings of dorsal horn neurons activity in vitro, for up to eight days. Paclitaxel application also induced increased Akt kinase phosphorylation in rat DRG neurons. All these paclitaxel-induced changes were prevented by the wortmannin in vivo pretreatment. Acute co-application of wortmannin or LY-294002 with paclitaxel in spinal cord slices also attenuated the paclitaxel effect on capsaicin-evoked responses. Staurosporine was effective in the acute in vitro experiments and on the first day after the paclitaxel treatment in vivo, but in contrast to wortmannin, it did not have a significant impact later. Our data suggest that the inhibition of PI3K signaling may help alleviate pathological pain syndromes in the paclitaxel-induced neuropathy.
Keywords: signální transdukce; Signal Transduction; kationtové kanály TRPV; onkogenní protein v-akt; inhibitory proteinkinas; toll-like receptor 4; lipopolysacharidy; Spinal Cord; Phosphatidylinositol 3-Kinases; Lipopolysaccharides; protein-serin-threoninkinasy; mícha; Toll-Like Receptor 4; krysa rodu Rattus; kationtové kanály TRP; Capsaicin; Hyperalgesia; zvířata; myši; myši inbrední C57BL; potkani Wistar; Mice; neuralgie; Peptide Fragments; Protein Kinase Inhibitors; Neuralgia; Protein Serine-Threonine Kinases; Rats, Wistar; Male; Posterior Horn Cells; Transient Receptor Potential Channels; fosfatidylinositol-3-kinasy; paclitaxel; Excitatory Postsynaptic Potentials; Mice, Inbred C57BL; Protein Kinase C; peptidové fragmenty; Rats; kapsaicin; hyperalgezie; proteinkinasa C; Animals; Paclitaxel; TRPV Cation Channels; excitační postsynaptické potenciály; mužské pohlaví; Oncogene Protein v-akt; buňky zadních rohů míšních